# What is the resulting equation when the expression for y in the second equation is substituted into the first equation? 3x + y = 1 y = 6 - 4x a. -x + 6 = 1 b. x + 6 = 1 c. 7x + 6 = 1

QUESTION POSTED AT 18/01/2020 - 07:14 AM

QUESTION POSTED AT 18/01/2020 - 07:14 AM

**Answer:**

When expression for y in the second equation is substituted into the first equation than the resulting equation -x + 6 = 1 .

Option (a) is correct .

**Step-by-step explanation:**

As given the equations in the questions are

3x + y = 1

y = 6 - 4x

As expression for y in the second equation is substituted into the first equation .

i.e put y = 6 - 4x in 3x + y = 1 .

3x + 6 - 4x = 1

Solving the above

-x + 6 = 1

Therefore the when expression for y in the second equation is substituted into the first equation than the resulting equation -x + 6 = 1 .

Option (a) is correct .

The answer is the A :)

30*3 and you'll get the number of minutes Reggie walked

30*3 and you'll get the number of minutes Reggie walked

ANSWERED AT 20/02/2020 - 10:02 AM

QUESTION POSTED AT 20/02/2020 - 10:02 AM

The standard equation for a hyperbola with a horizontal transverse axis is

(x-h)^2/a^2 - (y-k)^2/b^2 = 1 . The center is at (h, k) . The distance between the vertices is 2a . The distance between the foci is 2c and c^2 = a^2 + b^2. Therefore,

8^2 = 6^2 + b^2

b = 2√7

Assuming it is located at the origin.

(x-h)^2/a^2 - (y-k)^2/b^2 = 1

(x)^2/6^2 - (y)^2/(2√7)^2 = 1

**x^2/36 - y^2/28 = 1**

(x-h)^2/a^2 - (y-k)^2/b^2 = 1 . The center is at (h, k) . The distance between the vertices is 2a . The distance between the foci is 2c and c^2 = a^2 + b^2. Therefore,

8^2 = 6^2 + b^2

b = 2√7

Assuming it is located at the origin.

(x-h)^2/a^2 - (y-k)^2/b^2 = 1

(x)^2/6^2 - (y)^2/(2√7)^2 = 1

ANSWERED AT 20/02/2020 - 09:54 AM

QUESTION POSTED AT 20/02/2020 - 09:54 AM

G. is your answer have a nice evening

ANSWERED AT 19/02/2020 - 06:08 PM

QUESTION POSTED AT 19/02/2020 - 06:08 PM

24x-3+0.06x=4(6.7)

24.06x-3=26.8

24.06x=29.8

x=about 1.24

24.06x-3=26.8

24.06x=29.8

x=about 1.24

ANSWERED AT 19/02/2020 - 06:01 PM

QUESTION POSTED AT 19/02/2020 - 06:01 PM

Ok so some basic rules

so

so

ANSWERED AT 19/02/2020 - 05:17 PM

QUESTION POSTED AT 19/02/2020 - 05:17 PM

The answer would be B simply because it sounds more reasonable.

ANSWERED AT 19/02/2020 - 04:59 PM

QUESTION POSTED AT 19/02/2020 - 04:59 PM

**Answer:**

**Step-by-step explanation:**

We have been given an equation . we are asked to find the value of x that makes our given equation true.

Let us solve our given equation for x using opposite operations.

Subtract 8 from both sides:

Divide both sides by 4:

**Therefore, is the solution for our given equation.**

Let us verify our answer:

**Both sides are equal. Hence proven is solution for our given equation.**

ANSWERED AT 19/02/2020 - 04:35 PM

QUESTION POSTED AT 19/02/2020 - 04:35 PM

The answer is 20 because 5+5=10. 50-10=40. 40 divided by 2 = 20!

The answer is 20!

The answer is 20!

ANSWERED AT 19/02/2020 - 04:28 PM

QUESTION POSTED AT 19/02/2020 - 04:28 PM

Huh well, you can do 5 times x = 15 or 15/5 = x

x is the answer

x is the answer

ANSWERED AT 19/02/2020 - 03:57 PM

QUESTION POSTED AT 19/02/2020 - 03:57 PM

**Answer:**

**Option C is correct.**

The kind of growth model is shown in the table is exponential

**Step-by-step explanation:**

**Exponential growth function **is in the form of : ......[1]; where a is the initial value and b> 0.

**Consider any two point from the table:**

(1 , 5) and ( 2 , 25)

Substitute these in the equation [1] we get;

......[2]

......[3]

**Divide equation [3] by [2] we have;**

Simplify:

Now substitute this value in equation [2] we get;

Divide both sides by 5 we get;

Simplify:

1=a or a = 1

**Therefore, the table shown the exponential growth function is, **

ANSWERED AT 19/02/2020 - 03:44 PM

QUESTION POSTED AT 19/02/2020 - 03:44 PM

2 to the 3rd power equals 8. 2x2x2=8. 2x would then equal 16. 2x8=16.

ANSWERED AT 19/02/2020 - 03:27 PM

QUESTION POSTED AT 19/02/2020 - 03:27 PM

100% of a number would be 5 * 20.

5x

5x

ANSWERED AT 19/02/2020 - 02:47 PM

QUESTION POSTED AT 19/02/2020 - 02:47 PM

**Answer:**

b/50

**Step-by-step explanation: There were 150 students who donated a total of b books.**

**The students donated an average of b/150 books each.**

**Hannah donated 3 times as many books as the average.**

**b/150 * 3 = b/50**

**Hannah donated b/50 books.**

ANSWERED AT 19/02/2020 - 02:30 PM

QUESTION POSTED AT 19/02/2020 - 02:30 PM

Perpendicular lines will have negative reciprocal slopes. Example : if u r given a slope of 1/3, to find the negative reciprocal, flip the slope and change the sign. So the negative reciprocal of 1/3 is -3/1 or just -3. So slope 1/3 and slope -3 are perpendicular.

==================

equation 2 :

4x + 2y = 6

2y = -4x + 6

y = -2x + 3...the slope here is -2....a perpendicular line will have a slope of 1/2.

y = (a/3)x - 6......so we have to make a/3 = 1/2......1.5/3 = 1/2

so a = 1.5

===================

eq. 2 : 3/4x + 2

not sure what the entire equation is.....but it looks to have a slope of 3/4. That means a perpendicular line will have a slope of -4/3.

3y + ax = 9

3y = -ax + 9

y = (-a/3)x + 3.....therefore, a has to be 4

==================

equation 2 :

4x + 2y = 6

2y = -4x + 6

y = -2x + 3...the slope here is -2....a perpendicular line will have a slope of 1/2.

y = (a/3)x - 6......so we have to make a/3 = 1/2......1.5/3 = 1/2

so a = 1.5

===================

eq. 2 : 3/4x + 2

not sure what the entire equation is.....but it looks to have a slope of 3/4. That means a perpendicular line will have a slope of -4/3.

3y + ax = 9

3y = -ax + 9

y = (-a/3)x + 3.....therefore, a has to be 4

ANSWERED AT 19/02/2020 - 02:18 PM

QUESTION POSTED AT 19/02/2020 - 02:18 PM

Using any specific formula or what?

ANSWERED AT 19/02/2020 - 01:41 PM

QUESTION POSTED AT 19/02/2020 - 01:41 PM

The answer is D !!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

ANSWERED AT 19/02/2020 - 01:34 PM

QUESTION POSTED AT 19/02/2020 - 01:34 PM

For the answer to the question above,

1. If we let x as the side of the square cut-out, the formula for the capacity (volume) of the food dish is:

V = (12 - 2x)(8 - 2x)(x)

V = 96x - 40x^2 + 4x^3

To find the zeros, we equate the equation to 0, so, the values of x that would result to zero would be:

x = 0, 6, 4

2. To get the value of x to obtain the maximum capacity, we differentiate the equation, equate it to zero, and solve for x.

dV/dx = 96 - 80x + 12x^2 = 0

x = 5.10, 1.57

The value of x that would give the maximum capacity is x = 1.57

3. If the volume of the box is 12, then the value of x can be solved using:

12 = 96x - 40x^2 + 4x^3

x = 0.13, 6.22, 3.65

The permissible value of x is 0.13 and 3.65

4. Increasing the cutout of the box increases the volume until its dimension reaches 1.57. After that, the value of the volume decreases it reaches 4.

5. V = (q -2x) (p - 2x) (x)

1. If we let x as the side of the square cut-out, the formula for the capacity (volume) of the food dish is:

V = (12 - 2x)(8 - 2x)(x)

V = 96x - 40x^2 + 4x^3

To find the zeros, we equate the equation to 0, so, the values of x that would result to zero would be:

x = 0, 6, 4

2. To get the value of x to obtain the maximum capacity, we differentiate the equation, equate it to zero, and solve for x.

dV/dx = 96 - 80x + 12x^2 = 0

x = 5.10, 1.57

The value of x that would give the maximum capacity is x = 1.57

3. If the volume of the box is 12, then the value of x can be solved using:

12 = 96x - 40x^2 + 4x^3

x = 0.13, 6.22, 3.65

The permissible value of x is 0.13 and 3.65

4. Increasing the cutout of the box increases the volume until its dimension reaches 1.57. After that, the value of the volume decreases it reaches 4.

5. V = (q -2x) (p - 2x) (x)

ANSWERED AT 19/02/2020 - 01:10 PM

QUESTION POSTED AT 19/02/2020 - 01:10 PM

8=f/2=answer hope this helps

ANSWERED AT 19/02/2020 - 12:36 PM

QUESTION POSTED AT 19/02/2020 - 12:36 PM

1-b

2-c

good luck .......

2-c

good luck .......

ANSWERED AT 19/02/2020 - 12:22 PM

QUESTION POSTED AT 19/02/2020 - 12:22 PM

-- State-A . . . Population = 1 · (1.08)ˣ

-- State-B . . . Population = 2 · (1.08)ˣ

' x ' = number of years after the original population

At the beginning, x=0.

Any quantity raised to the zero power = 1.

At the beginning, when x=0, the original populations were

State-A = 1 · 1 = 1

State-B = 2 · 1 = 2

The original population of State A**was half** of

the original population of State B.

-- State-B . . . Population = 2 · (1.08)ˣ

' x ' = number of years after the original population

At the beginning, x=0.

Any quantity raised to the zero power = 1.

At the beginning, when x=0, the original populations were

State-A = 1 · 1 = 1

State-B = 2 · 1 = 2

The original population of State A

the original population of State B.

ANSWERED AT 19/02/2020 - 11:53 AM

QUESTION POSTED AT 19/02/2020 - 11:53 AM

B. Calculate the value of MN

ANSWERED AT 19/02/2020 - 11:52 AM

QUESTION POSTED AT 19/02/2020 - 11:52 AM

-3x -7 + 4x + 7

= 4x - 3x - 7 + 7

= x - 7 + 7

= x

Or.. if your are doing it this way then it would be

(-3 * -7) + (4 +7)

= 3 * 7 + 4 +7

= 21 + 4 + 7

= 32

Hope these help! :)

= 4x - 3x - 7 + 7

= x - 7 + 7

= x

Or.. if your are doing it this way then it would be

(-3 * -7) + (4 +7)

= 3 * 7 + 4 +7

= 21 + 4 + 7

= 32

Hope these help! :)

ANSWERED AT 19/02/2020 - 11:44 AM

QUESTION POSTED AT 19/02/2020 - 11:44 AM

.237 would be the answer though it's not a terminating decimal.

ANSWERED AT 19/02/2020 - 11:43 AM

QUESTION POSTED AT 19/02/2020 - 11:43 AM

X+1 or 1+x because 1 multiply x is x

ANSWERED AT 19/02/2020 - 11:30 AM

QUESTION POSTED AT 19/02/2020 - 11:30 AM

It stands for the number **6**

hope this helps you

hope this helps you

ANSWERED AT 19/02/2020 - 11:29 AM

QUESTION POSTED AT 19/02/2020 - 11:29 AM

Substitue y=3x into the other equation to get 3x=-x+4. Solve this to get 4x=4 therefore x=1.

knowing this, y=3

knowing this, y=3

ANSWERED AT 19/02/2020 - 11:22 AM

QUESTION POSTED AT 19/02/2020 - 11:22 AM

12^x = 22

x * log 12 = log 22

finsih that then you round it to the nearest thousandth

that's what i learnt.

x * log 12 = log 22

finsih that then you round it to the nearest thousandth

that's what i learnt.

ANSWERED AT 19/02/2020 - 11:21 AM

QUESTION POSTED AT 19/02/2020 - 11:21 AM

I hope this helps you

(f.g) (x)=(-2x+7)(-6x+3 )

(f.g)(x)=12x^2-6x-42x+21

(f.g)(x)=12x^2-48x+21

A

(f.g) (x)=(-2x+7)(-6x+3 )

(f.g)(x)=12x^2-6x-42x+21

(f.g)(x)=12x^2-48x+21

A

ANSWERED AT 19/02/2020 - 10:19 AM

QUESTION POSTED AT 19/02/2020 - 10:19 AM

X=-1 is the answer i beleive

ANSWERED AT 19/02/2020 - 09:42 AM

QUESTION POSTED AT 19/02/2020 - 09:42 AM

Y - y1 = m(x - x1)

slope(m) = -1/2

(-4,-2)...x1 = -4 and y1 = -2

now we sub

y - (-2) = -1/2(x - (-4) =

y + 2 = -1/2(x + 4) <=====

slope(m) = -1/2

(-4,-2)...x1 = -4 and y1 = -2

now we sub

y - (-2) = -1/2(x - (-4) =

y + 2 = -1/2(x + 4) <=====

ANSWERED AT 19/02/2020 - 01:12 AM

QUESTION POSTED AT 19/02/2020 - 01:12 AM